Returning to play after coronavirus infection: Pediatric cardiologists' perspective - Dean, P. N.; Jackson, L. B.; Paridon, S. M. (American College of Cardiology, 2020)
- Returning to sports participation after a COVID infection will be a significant question posed to pediatric providers in the coming months. - The approach to sports participation clearance in pediatric patients should differ from the approach in adult patients. - Most pediatric patients will be able to be easily cleared for participation without extensive cardiac testing, but pediatric providers should ensure patients have fully recovered and have no evidence of myocardial injury.